MODEL MATEMATIKA PENYAKIT HEPATITIS B DENGAN PENGARUH TRANSMISI VERTIKAL - Desti Asriyah; Norma Muhtar; Arman (Jurusan Matematika FMIPA Universitas Halu Oleo, 2024)
Hepatitis B is an infectious disease caused by a virus (HBV). This virus is one type of many viruses that attack the liver. This study aims to discuss the mathematical model of hepatitis B disease with the effect of vertical transmission. From the results of the analysis obtained two disease-free balance points and endemic balance points. Furthermore, an analysis of the behavior of the solution is carried out using the eigenvalues and the properties of stability at the equilibrium point, the result is that the disease-free equilibrium point has two stability properties, namely saddle point and stable. The disease-free equilibrium point will be stable if R0 < 1, if R0 > 1 then the equilibrium point is unstable (saddle point) and conversely the positive endemic equilibrium point will be stable. The numerical analysis was carried out by varying the parameter values and using the fourth-order Runge-Kutta approach